Engineered wood products as substitutes in the Canadian building construction industry. (16th February 2021) - Shahi, Shashi K.; Leitch, Mathew; Dia, Mohamed
Engineered and reconstituted wood products play an important role in building construction, and have positive environmental impacts. However, the wood products compete with other construction material (concrete and steel) in terms of prices in the Canadian building construction industry, and the price competition has not been explored in past literature. In order to promote the use of wood and wood-based products, there is a need to understand how prices influence the choice of construction material. We estimated the own and cross-price elasticities of demand of construction material in Canada using standard log-linear regression models with consumption and price data from 1990 to 2017. Our study shows that engineered and reconstituted wood products are substitutes for cement and steel, and hence there is a need to focus on the development of these value-added forest products, to create sustainable local economies that are economically viable, environmentally sound and socially responsible.